Effect of urinary excretion on radiation dose in patients having PET/CT scans - Gül, Serdar Savaş; Esen, Mehmet (The European Research Journal, 2019)
Objectives: 18Fluorine-fluorodeoxyglucose (18F-FDG) positron emission tomography/ computed tomography (PET/CT) is commonly used for diagnosis, staging and re-staging of cancers and for determining the effectiveness of treatment. Because of renal, ureteral and urinary involvement of 18F-FDG radiopharmaceutical after its injection, patients subject to radioactivity during its effective half-life. The aim of the present study was to determine the degree of association between effective dose levels of patients and bladder emptying of patients having PET/CT scans. Methods: The present retrospective study included 108 patients (43 females and 65 males, average age: 60.9 ± 12.7 years). Effective dose level as mSv/h was determined from a distance of 1 m in all patients before and after bladder emptying at the first hour following 18F-FDG injection. Radioactivity excretion amounts were compared based on gender, age, body mass index, fasting blood sugar level and clinical diagnosis. Results: Amount of radioactivity decreased by 22.75% ± 14.77% after bladder emptying. No association was found between urinary excretion level and age, gender, fasting blood sugar and body mass index (p > 0.05). Conclusions: Active emptying of bladder in patients having PET/CT scans where 18F-FDG radiopharmaceutical is involved is an effective method for the radiation safety of both health workers and patients.